ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI PULAU JAWA DAN SUMATERA - Inda Hadi; Husnul Khotimah (Universitas Trilogi, 2022)
The purpose of this research is to analyze the financial performance of regional governments in the provinces of Java and Sumatra using regional financial ratios. The goal of this research is to compare the financial performance of the islands of Java and Sumatra from 2015 to 2019. The study method employed was descriptive quantitative. The data used is from each province's Budget Realization Report for 2015-2019. Documentation is the method utilized to acquire data. In this study, the T-test was used to evaluate hypotheses using SPSS 26. The findings of this study show that: The financial performance of the Java Island province, as measured by the independence ratio, is moderate whereas Sumatra Island's is poor. The province of Java is categorized as extremely effective, whereas Sumatra Island is classified as effective. The financial performance of Java Island is classed as inefficient by the efficiency ratio, whereas Sumatra Island is labeled as inefficient. The independence ratio is significantly different, the average efficiency ratio and the efficiency ratio are not significantly different, according to the Independent Sample T-test. The results of the study indicate that it is still necessary to make efforts to improve performance in the provinces in Java and Sumatra so that the goal of establishing regional autonomy can be achieved. Keywords: effectiveness ratio; efficiency ratio; financial performance; independence ratio